Corona Crisis and Inequality: Why Management Research Needs a Societal Turn - Bapuji, Hari; Patel, Charmi; Ertug, Gokhan; Allen, David G. (Journal of management, 2020)
As the world struggles to deal with the COVID-19 pandemic, the stark inequalities in our societies have been laid bare, and the interplay between organizations and societies has also become evident yet again. This crisis underscores the need for management scholars to take a societal turn and examine how organizational practices interact with societal economic inequality. To illustrate this approach, we discuss organizational practices—corporate social responsibility, work design, recruitment and selection, and compensation management—that can contribute to the normalization, reinforcement, and reduction of economic inequalities in society. We conclude by calling on scholars of inequality, as well as of broader management research, to take a societal turn to enhance the relevance and impact of management research.